2016
DOI: 10.18869/ijabbr.2016.245
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of yeast species from ensete ventricosum product; Kocho and Bulla collected from Angacha district

Abstract: Kocho and Bula are fermented product of Enset (Ensete ventricosum). It is the staple food for 20 million people in Ethiopia. The aim of study was to isolate, identify and characterize yeast species from fermented kocho and bulla by using Biolog Micro station. 300 Kocho samples were collected from Angacha District. 0.1ml of serially diluted samples were Streaked on yeast pepton dextrose agar and incubated at 28 0 C. Pure yeast colony inoculum were prepared at 9ml distilled water at 49% +2 turbidometer and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…Indeed, species of the order Oscillatoriales are apparent in hot springs of temperature ranging from 40 to 66 °C (Pentecost, 2014(Pentecost, , 2003Pentecost et al, 2003) and their exopolysaccharide sheath is probably the backbone of the microbial mat developed (Abdelwahab and Amin, 2018). It has been reported that most conspicuous species of cyanobacteria in hot springs of temperature ranging from 40 to 66 °C belong to the order Oscillatoriales (Abdelwahab and Amin, 2017) that agrees with Oscillatoria as the prevailing genus in Al-Lith springs. Furthermore, the occurrence of filamentous cyanobacteria belonging to the Oscillatoriales in sulfur-rich environments of Al-Lith springs is well documented (Mohamed, 2008;Spring et al, 2003).…”
Section: Discussionsupporting
confidence: 60%
“…Indeed, species of the order Oscillatoriales are apparent in hot springs of temperature ranging from 40 to 66 °C (Pentecost, 2014(Pentecost, , 2003Pentecost et al, 2003) and their exopolysaccharide sheath is probably the backbone of the microbial mat developed (Abdelwahab and Amin, 2018). It has been reported that most conspicuous species of cyanobacteria in hot springs of temperature ranging from 40 to 66 °C belong to the order Oscillatoriales (Abdelwahab and Amin, 2017) that agrees with Oscillatoria as the prevailing genus in Al-Lith springs. Furthermore, the occurrence of filamentous cyanobacteria belonging to the Oscillatoriales in sulfur-rich environments of Al-Lith springs is well documented (Mohamed, 2008;Spring et al, 2003).…”
Section: Discussionsupporting
confidence: 60%
“…Characterizing and standardizing the bacteria and yeast species currently used in enset fermentation is important for improving quality and consistency of food products and supporting the development of an effective standard set of starter cultures. Gizaw, Tsegaye, and Tilahun () isolated seven non‐Saccharomyces yeast species from fermented kocho and bulla samples, using metabolic and morphological character similarity to identify them as; Cryptococcus albidus var. aerus , Guilliermondella selenospora, Rhodotorula acheniorum and Trichosporon beigelii , Cryptococcus terreus (99%), Candida zylandase (98%) and Kluyveramyces delphensis (86%).…”
Section: Processing Methods Products and Cultural Importancementioning
confidence: 99%
“…Ashenafi () and Tafere (), in general reviews of fermented products in Ethiopia, highlighted the value of controlled fermentation studies with selected cultures and starters to optimize the processes involved. Both Hunduma and Ashenafi () and Gizaw et al () recommended that this could reduce labor for women, help to avoid spoilage during fermentation, improve the long‐term storage and product quality, and reduce waste and increase food security.…”
Section: Processing Methods Products and Cultural Importancementioning
confidence: 99%
“…In most of these studies, identification was not done using molecular techniques, instead, less reliable physiological and morphological characteristics have been used for species identification, both for bacteria and yeasts. Yeasts were in many cases only identified to the genus level and frequently invalid taxonomic terms were used, making it impossible to draw any conclusion about the role of yeast species in kocho fermentation (Gashe 1987a , b ; Gizaw et al 2016 ; Tsegay et al 2016 ). Very recently, Andeta et al ( 2018 ), used 16S ribosomal RNA (rRNA) gene sequencing to identify bacteria from enset samples within the range of one to 60 days of fermentation period.…”
Section: Introductionmentioning
confidence: 99%